The Implementation Of Android-Based Game "Climbing Castle" To Improve Grammar Mastery: A Classroom Action Research To Grade 8 Students At Smpn 3 Sutojayan Blitar - Sutanti, Nita; Ulum, Bahrul; Farinawati, Yeni (JOSAR (Journal of Students Academic Research), 2024)
This classroom action research aims to enhance the grammar mastery of Grade 8 students at SMPN 3 Sutojayan through the implementation of the Android-based game "Climbing Castle." The study was conducted over a cycle, consisting of planning, action, observation, and reflection phases. Data were collected using tests, observations, and interviews to evaluate students' progress and engagement. The results indicate a significant improvement in students' grammar mastery, with increased motivation and participation in learning activities. The increasing opf Students’ motivation affect the students’s score in learning grammar by 42%. The interactive and engaging nature of the "Climbing Castle" game proved to be an effective tool in creating a conducive learning environment, thus facilitating better grammar comprehension among students. This research highlights the potential of educational games in enhancing language learning outcomes and suggests further exploration into integrating technology-based methods into the curriculum. Further research is needed to investigate the effectiveness of Android Based game, Climbing Castle, in different contexts and with different groups of students.